Outward depolarization of the microglia mitochondrial membrane potential following lipopolysaccharide exposure: a novel screening tool for microglia metabolomics - McGlothen, Kendra I.; Hines, Rochelle M.; Hines, Dustin J. (Frontiers in Cellular Neuroscience, 2024)
Microglia are non-electrogenic immune cells that respond rapidly to protect the central nervous system (CNS) from infections, injuries, or other forms of damage. Microglia mitochondria are essential for providing the requisite energy resources for immune regulation. While fluctuations in energy metabolism are regulated by mitochondria and are reflected in the mitochondrial membrane potential (ΔΨm), there remains a lack of innovation in microglia-centric tools that capitalize on this. In this study, live imaging of microglia in acute slices from EGFP reporter mice expressing EGFP under the control of the fractalkine receptor (CX3CR1) promoter is combined with loading a fluorescent reporter of ΔΨm. Depolarizations in the ΔΨm were recorded after administering the wellcharacterized immune stimulant lipopolysaccharide (LPS). Microglia ΔΨm increased in distinctive phases with a relatively steep slope following LPS exposure. Conversely, the ΔΨm of neurons showed minimal regulation, highlighting a distinct microglia ΔΨm response to immune stimuli. Analysis of the depolarization of the microglia ΔΨm in the soma, branches, and endfeet revealed progressive changes in each subcellular domain originating in the soma and progressing outward. The inverse agonist emapunil attenuated the depolarization of the ΔΨm across states in a domainspecific manner. These findings emphasize the contribution of mitochondrial membrane dynamics in regulating microglial responses to immune stimuli. Further, this work advances a novel drug screening strategy for the therapeutic regulation of metabolic activity in inflammatory conditions of the brain.